2004
DOI: 10.1111/j.0141-9838.2004.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

The immunoepidemiology of human hookworm infection

Abstract: Advances in hookworm immunoepidemiology are reviewed. Recent studies demonstrate a mixed Th1/Th2 response in human hookworm infection, with immunosuppression of specific and nonspecific IFN-gamma responses. There is increasing evidence for protective immunity in human hookworm infection, including anti-larval IL-5- and IgE-dependent mechanisms, and for immunological interactions between hookworm infection and other diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 86 publications
(152 reference statements)
3
45
0
Order By: Relevance
“…It has previously been noted that infected individuals from endemic populations exhibit strong humoral response to various worm antigens and that certain immunoglobulin subtypes may be more closely associated with infection status. [74][75][76][77] The serologic data presented here show that ES proteins from the human and animal hookworm A. ceylanicum [25][26][27] can serve as useful reagents for measuring parasite-specific antibody responses in subSaharan Africa. This finding confirms significant cross-reactivity between ES proteins of A. ceylanicum and those from the two most common human hookworm species in Ghana, A. duodenale and N. americanus .…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been noted that infected individuals from endemic populations exhibit strong humoral response to various worm antigens and that certain immunoglobulin subtypes may be more closely associated with infection status. [74][75][76][77] The serologic data presented here show that ES proteins from the human and animal hookworm A. ceylanicum [25][26][27] can serve as useful reagents for measuring parasite-specific antibody responses in subSaharan Africa. This finding confirms significant cross-reactivity between ES proteins of A. ceylanicum and those from the two most common human hookworm species in Ghana, A. duodenale and N. americanus .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike what has been traditionally thought for most other helminths, immunoepidemiological studies in hookworm endemic areas suggest that hookworms elicit a 'mixed' Th1/Th2 cell response in which both Th1, interferon-g (IFN-g) and IL-12, and Th2 (IL-4, IL-5 and IL-13) cytokines are produced [7,11]. This is also unlike what has been shown experimentally with hookworm and hookworm-related species since these studies have shown a typical Th2 response against infection [27,43,44,46e48].…”
Section: Response Against Hookworm Infection and Hookworm-related Spementioning
confidence: 94%
“…In common with other helminth infections are elevated levels of total and specific antibody and eosinophilic responses [3,7,11,14,16,49]. The vigorous antibody response is directed to both larval and adult antigens, and is characterized by the production of all five human isotypes [6], although IgG4 and IgE are the most prominent and have been shown to be correlated to chronicity (or duration) of the infection [9,11].…”
Section: Response Against Hookworm Infection and Hookworm-related Spementioning
confidence: 99%
“…Negative associations have been observed between hookworm parasite burden and parasite-specific IgG, IgM and IgE antibody levels (17)(18)(19). Children living in endemic areas of Brazil and who appear to be resistant to hookworm infection produce greater levels of both type-1 (IFN-c) and type-2 cytokines compared with chronically infected children (20), and a treatment study of infected adults from a highly endemic area of Papua New Guinea provided evidence that resistance to reinfection following treatment was associated with the type-2 cytokine, IL-5 (21).…”
Section: Hookwormmentioning
confidence: 99%